Discussion and Deliberation on the Latest ISO 6336 Standard - Liu Zhongming Li Youhua Zhang Zhihong Ding Wei Chen Chao (Jixie chuandong)
Compared with ISO 6336:1996 edition，there are great changes in the latest edition of ISO/FDIS 6336-1 to 3：2019, in particular, the calculation of the helix angle factor for helical gear has a subversive change. In order to facilitate the reader to understand the changes of the new ISO 6336, the main changes in the content of different editions of ISO 6336 are introduced, the influences of the helix angle factors and single pair tooth contact factor on safety factor before and after modification are analyzed, and the influence of helix angle on the calculation results of contact strength and bending strength are discussed here with examples.